2021
DOI: 10.3390/s21062157
|View full text |Cite
|
Sign up to set email alerts
|

Integration of 3D Printed Flexible Pressure Sensors into Physical Interfaces for Wearable Robots

Abstract: Sensing pressure at the physical interface between the robot and the human has important implications for wearable robots. On the one hand, monitoring pressure distribution can give valuable benefits on the aspects of comfortability and safety of such devices. Additionally, on the other hand, they can be used as a rich sensory input to high level interaction controllers. However, a problem is that the commercial availability of this technology is mostly limited to either low-cost solutions with poor performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…More specifically, it is known that the variability of EMG signals can be significant across time due to artefacts and crosstalk (Bi et al, 2019 ). On the other hand, we found that pressure measurements are generally more stable signals across a particular pattern, which is in line with previous research on the topic (Connan et al, 2016 ; Langlois et al, 2021 ). This leads us to expect the pressure sensing would improve a more general motion classification across a large sample size as well.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…More specifically, it is known that the variability of EMG signals can be significant across time due to artefacts and crosstalk (Bi et al, 2019 ). On the other hand, we found that pressure measurements are generally more stable signals across a particular pattern, which is in line with previous research on the topic (Connan et al, 2016 ; Langlois et al, 2021 ). This leads us to expect the pressure sensing would improve a more general motion classification across a large sample size as well.…”
Section: Discussionsupporting
confidence: 93%
“…At the beginning of every trial the sensors are calibrated relative to the force sensing of the cobot. The design of the pressure sensors and the calibration process are described in detail in Langlois et al ( 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand comfort, several studies have quantified interaction forces/pressures at the user-exoskeleton interface, or assessed contact pressures with different physical interface designs or materials. [43][44][45][46][47] Levesque et al, 43 in particular, offered several interface design recommendations, including a cuff that can accommodate large inter-and intra-subject variability in limb shape and dimensions, as well as changes due to muscle contraction, and that can tilt to maintain broad contact regardless of body segment movements. Kozinc et al 45 reported that pressure tolerance is highly variable between individuals, and lower for women.…”
Section: Concerns About Ase Design and Physical Interfacementioning
confidence: 99%
“…It was shown that effort expectancy affects exoskeleton acceptance [34], suggesting that the worker's preferred tool is likely to be the tool that is easy to use, optimizing the worker's well-being and overall performance without compromising its natural kinematics or comfort [35], [36], while it also reduces the physical workload. This is a delicate balance, as higher torques result in higher forces applied on the body, and higher pressures at the level of the human-robot interfaces, which were associated with discomfort [37], [38].…”
mentioning
confidence: 99%